Konflik Hukum di Sektor Pertambangan: Perspektif Pengelolaan Sumber Daya Alam yang Berkelanjutan - Zulkarnain Zulkarnain (Syntax Literate, 2023)
Sustainable management of natural resources is one of the major challenges faced by Indonesia, one sector that is often a source of conflict is the mining sector. The purpose of this study is to analyze the factors that cause legal conflicts in the mining sector in Indonesia and examine the implications of legal conflicts for sustainable natural resource management. This research uses qualitative research methods. Data collection techniques in this research using literature studies. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation and conclusion drawing. The results showed that legal conflicts in the mining sector in Indonesia were caused by several factors, including unfair profit sharing, environmental damage, and violations of community rights. Legal conflicts in the mining sector have negative implications for sustainable natural resource management. Legal conflicts can hamper investment, reduce productivity, and damage the environment.